Estimation of Thermokinetics of Sorption of Mercury (II) Iodide Complexes on Sulphocationite KU-2-8 Modified by Crystal Violet - E. A. Zauer (Challenges and Advances in Chemical Science Vol. 8, 2022)
The kinetics of sorption of iodide complexes of mercury (II) on sulfonic cation exchanger KU-2-8 modified with a basic crystal violet dye was studied by microcalorimetric method. It was found that the order of the sorption process is close to the first. The rate constant is 2.66 · 10-3 s-1. The activation energy is 16.6 kj / mol, which indicates the predominance of the sorption mechanism of external diffusion. The pre-exponential factor is 0.261.